The Role Of The Lecturer In Communicating Collaborative Strategies: To Meet Challenges And Solutions In The Integration Of Nursing, Anesthesia And Pharmacy (Journal of Namibian Studies : History Politics Culture, 2024)
The healthcare system has been challenged for many years by a variety of factors throughout the world. Some of these challenges include an ever-growing population, aging populations, advances in medical technologies, and more recently, the COVID-19 pandemic. The problems persistently raised include accessibility, affordability, quality, and safety of services delivered to patients. Addressing these issues without compromising quality has become more complex and made client, healthcare employee, and government expectations on the healthcare system more demanding.